An Information Theory Approach to Identifying a Representative Subset of Hydro‐Climatic Simulations for Impact Modeling Studies. Issue 8 (16th August 2018) - Pechlivanidis, I.G.; Gupta, H.; Bosshard, T.
Abstract: Uncertainties in hydro‐climatic projections are (in part) related to various components of the production chain. An ensemble of numerous projections is usually considered to characterize the overall uncertainty; however in practice a small set of scenario combinations are constructed to provide users with a subset that is manageable for decision‐making. Since projections are unavoidably uncertain, and multiple projections are typically informationally redundant to a considerable extent, it would be helpful to identify an informationally representative subset in a large model ensemble. Here a framework rooted in the information theoretic Maximum Information Minimum Redundancy concept is proposed for identifying a representative subset from an available ensemble of hydro‐climatic projections. We analyze an ensemble of 16 precipitation and temperature projections for Sweden, and use these as inputs to the HBV hydrological model to project river discharge until the mid of this century. Representative subsets are judged in terms of different statistical properties of three essential climate variables (precipitation, temperature and discharge), whilst we further assess the sensitivity of the optimized subset for different seasons and future periods. Our results indicate that a quarter to a third of the available set of projections can represent more than 80% of the total information of hydro‐climatic changes. We find that the representative subsets are sensitive to the regional hydro‐climatic characteristics and the choice of variables, seasons and periods of interest. Therefore we recommend that any selection process should not be solely driven by climatic variables but, rather, should also consider variables of the impact model. Plain Language Summary: The need for better understanding of climate change and its impact has led to an increasing number of climate models and consequently hydro‐climatic projections. Using a large set of projections, we present the information content and the redundant information when an ensemble is considered, and hence demonstrate how representative projections can be identified in order to overcome artifacts/biases introduced by a common hand‐picking approach. An identified subset reduced by almost 70% from the large ensemble is capable of representing more than 80% of the total information for precipitation, temperature and discharge; however the selected projections are sensitive to choice of variables, seasons, and period of interest. The size of the representative subset is also related to the regional hydro‐climatic characteristics. Key Points: Redundant information is present in large model ensembles; subsets should target towards maximizing independence and minimizing redundancy A subset of 20–35% of the total available projections can represent a large fraction of the ensemble range for hydro‐climatic changes The identified subsets are sensitive to the choice of variables, seasons and future periods